2015
DOI: 10.1128/iai.00144-15
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the Transcription Factor Hypoxia-Inducible Factor 1α (HIF-1α) in Macrophages Accelerates the Necrosis of Mycobacterium avium-Induced Granulomas

Abstract: eThe establishment of mycobacterial infection is characterized by the formation of granulomas, which are well-organized aggregates of immune cells, namely, infected macrophages. The granuloma's main function is to constrain and prevent dissemination of the mycobacteria while focusing the immune response to a limited area. In some cases these lesions can grow progressively into large granulomas which can undergo central necrosis, thereby leading to their caseation. Macrophages are the most abundant cells presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 54 publications
(63 reference statements)
2
31
0
Order By: Relevance
“…That MDSCs themselves have been implicated as IL-17 producers during Mtb infection (37) suggests that IL-17 made by MDSCs may be a necessary feedback loop to limit excessive HIF1α production in MDSCs. Interestingly, in a systemic Mycobacterium avium model of infection, mice deficient in HIF1α expression in myeloid cells demonstrated increased liver necrosis (39). A recent study also showed that in a high-dose model of Mtb Erdman infection, mice deficient in HIF1α in myeloid cells demonstrated increased susceptibility to infection (40).…”
Section: Discussionmentioning
confidence: 84%
“…That MDSCs themselves have been implicated as IL-17 producers during Mtb infection (37) suggests that IL-17 made by MDSCs may be a necessary feedback loop to limit excessive HIF1α production in MDSCs. Interestingly, in a systemic Mycobacterium avium model of infection, mice deficient in HIF1α expression in myeloid cells demonstrated increased liver necrosis (39). A recent study also showed that in a high-dose model of Mtb Erdman infection, mice deficient in HIF1α in myeloid cells demonstrated increased susceptibility to infection (40).…”
Section: Discussionmentioning
confidence: 84%
“…First, it was demonstrated that pharmacological stabilization of HIF-1α during infection of zebrafish embryos with M. marinum leads to a reduced bacterial burden at early timepoints (19). Second, HIF-1α was found to play a role in a mouse model of granuloma caseation in livers of mice infected with M. avium (20). This granuloma formation depends upon hypoxia but is independent of effectors of IFN-γ based immunity, including NO.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously increasing the levels of active HIF-1α using pharmacological or genetic tools in zebrafish embryos enhances bactericidal activity against Mycobacterium marinum (19). Mice lacking HIF-1α in the myeloid lineage exhibit more rapid progression of hypoxic granulomatous lesions in the liver following intravenous infection with Mycobacterium avium (20). These data suggest the intriguing possibility that HIF-1α may be an important mediator of resistance to M. tuberculosis infection.…”
Section: Introductionmentioning
confidence: 99%
“…Following this study, several other groups reported the importance of HIF-1α in pathogen clearance by myeloid cells during bacterial infections. For instance, myeloid conditional HIF-1α knockout mice fail to clear Mycobacterium infection and develop earlier emergence of necrosis in the granuloma [102]. HIF-1α is also required for effector neutrophil activity in keratitis and is fundamental for effective bacterial killing and antimicrobial peptide production during Pseudomonas aeruginosa infection [103].…”
Section: Hif-1α and Microbial Infectionsmentioning
confidence: 99%